Operárias da madeira: Trabalho, memórias e identidade (TEL Tempo, Espaço e Linguagem, 2023)
The aim of this article is to discuss the participation of women in the wood sector in Guarapuava, in the years 1980-2007, based on recollections of former wood workers IBEMA/Coralplac. We seek to historicize the entry of women into this sector and what work and family relationships were like. The memories presented here are about everyday life and gender relations experienced by working women who sought to survive and improve their living conditions, themselves and their families. These women built their identity as workers, identify themselves in this way and proudly position themselves as they are. Therefore, we present the situation of the timber sector in the 1980s, when these women were hired by the timber company, in order to contextualize the situation of the first female workers who entered the sector. And finally understand how this process was challenging for the workers and their families who depended on the company as a source of survival.